Penghambatan Xantin Oksidase Oleh Gel Ekstrak Takokak (Solanum torvum Swartz) Berbasis Nanoteknologi Secara In Vitro - Dwiyansyah, Muhammad Imam; Insyira, Rania; Mirsa, Almira Maurilla; Sawalia, Azzara Gita; Nugra, Daffa; Salmi, Salmi (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Inhibition of xanthine oxidase is one of the strategies in handling gout. This study aims to explore the potential of takokak fruit extract (Solanum torvum Swartz) in inhibiting nanotechnology-based xanthine oxidase in the form of nanoemulgel. This research is an experimental study conducted in several stages, namely qualitative phytochemical tests, quantitative identification of total flavonoid content and preparation of nanoemulgel made with 3.75% extract with variations of surfactant Tween 80 and PEG 400, namely F1 (30:30), F2 (35:25) and F3 (40:20). The ability of the extract and nanoemulgel was evaluated in inhibiting xanthine oxidase. The results showed that the ethanol extract of takokak fruit contained flavonoids, saponins, phenolics and tannins qualitatively. The total flavonoid content in the extract was 4.472 Â± 0.133 mgQE. Formulation F2 has the smallest particle size (18.5 nm) and polydispersity index of 0.1313. Takokak fruit extract has almost the same inhibitory power as allupurinol with an IC50 value of 45.54 ppm. The IC50 value of nanoemulgel 3.75% takokak extract is 29.26 ppm so that the IC50 of the extract in nanoemulgel form is 1.10 ppm (45 times the IC50 of the crude extract). In conclusion, Formula F2 is the best formula in the preparation of nanoemulgel with particle size and polydispersion index and strong xanthin oxidase inhibitory activity.